The Interaction of Craniofacial Morphology and Body Mass Index in Obstructive Sleep Apnea - Federica Bertuzzi; Antonio Santagostini; Matteo Pollis; Fabio Meola; Marzia Segù (MDPI AG, 2022)
Aim: This study sets out to explore the relationship between craniofacial morphology and obstructive sleep apnea (OSA) severity, assessing the relative contribution of obesity, calculated using BMI. Methods: A sample of 30 adult patients (20 males; 10 females), mean age = 54(±76) years, with a polysomnography-confirmed diagnosis of OSA, i.e., with an apnea-hypopnea index (AHI) of over 5 events/h, was recruited and underwent cephalometric evaluation. Sleep parameters, namely AHI, AHI supine, oxygen desaturation index (ODI), and mean oxygen saturation [Mean SaO2%], were assessed. Correlation analysis between 13 cephalometric features and AHI was performed using a Pearson test. The sample was split into three groups based on AHI score (mild = 10 < AHI < 15; moderate = 15 < AHI < 30; severe = AHI > 30), and ANOVA was performed to compare the means of cephalometric features. In addition, the sample was split into two groups according to BMI (normal weight = BMI < 25; overweight = BMI > 25). Correlation analysis between cephalometric features and AHI was performed for each group using a Pearson test. Results: The average polysomnographic values were AHI = 29.08(±16); AHI supine = 43.45(±21); ODI = 23.98(±21); mean SaO2(%) = 93.12(±2). Posterior facial height (PFH) was significantly lower in the severe OSA group than in patients with moderate OSA (p = 0.05). In the normal-weight group, negative correlations of the PFH and SNA angle with AHI (r = −0.36; r = −0.25, respectively), and positive correlations of the FMA angle and MP-H distance with AHI (r = 0.29; r = 0.20, respectively), were found. In the overweight group, negative correlations of AO-BO distance, SPAS (upper posterior airway space) and PAS (posterior airway space) with AHI (r = −0.30; r = −0.28; r = −0.24, respectively), and positive correlations of AFH (anterior facial height) and the FMA angle with AHI (r = 0.32; r = 0.25, respectively), emerged. Conclusions: PFH seems to be related to the aggravation of OSA. In normal-weight subjects, hard tissue-related factors have a greater impact on OSA severity, whereas in overweight subjects, the impact of fat tissue is greater.